Diagnostic medical parasitology - Garcia, Lynne Shore (ASM Press, 2016)
Covers all aspects of human medical parasitology and provides detailed, comprehensive, relevant diagnostic methods in one volume. The sixth edition incorporates newly recognized parasites, discusses new and improved diagnostic methods, and relevant regulatory requirements.